2016
DOI: 10.1371/journal.pbio.1002336
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes Mediate LTB4 Release during Neutrophil Chemotaxis

Abstract: Leukotriene B4 (LTB4) is secreted by chemotactic neutrophils, forming a secondary gradient that amplifies the reach of primary chemoattractants. This strategy increases the recruitment range for neutrophils and is important during inflammation. Here, we show that LTB4 and its synthesizing enzymes localize to intracellular multivesicular bodies that, upon stimulation, release their content as exosomes. Purified exosomes can activate resting neutrophils and elicit chemotactic activity in a LTB4 receptor-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(158 citation statements)
references
References 58 publications
9
143
1
1
Order By: Relevance
“…Chemokinecontaining exosomes derived from heat-stressed tumor cells are known to be chemoattractant to dendritic cells. 40 Majumdar et al 21 reported that exosomes secreted from neutrophils synthesize and carry the chemoattractant leukotriene B 4 (LTB4). This LTB4 on exosomes facilitates chemotaxis of neutrophils toward fMLP in both an autocrine and paracrine manner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemokinecontaining exosomes derived from heat-stressed tumor cells are known to be chemoattractant to dendritic cells. 40 Majumdar et al 21 reported that exosomes secreted from neutrophils synthesize and carry the chemoattractant leukotriene B 4 (LTB4). This LTB4 on exosomes facilitates chemotaxis of neutrophils toward fMLP in both an autocrine and paracrine manner.…”
Section: Resultsmentioning
confidence: 99%
“…20 In neutrophils, autocrine generation of bioactive lipids on exosomes enhances motility toward the chemoattractant N-formyL-MethionyL-LeucyL-Phenylalanine (fMLP). 21 In a previous report, 6 we showed that inhibition of exosome secretion by knockdown of Rab27a, Synaptotagmin7 or Hrs in cancer cells inhibits in vivo metastasis and motility of cancer cells in a chick embryo model system. In this model, exosome secretion controlled both cell speed and directionality; however the directional cues were unclear.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…During the inflammation neutrophils may also contribute to subsequent remodeling. Here, the LTB 4 -induced neutrophil chemotaxis, their released exosomes contain LTB 4 and its synthesizing enzymes [137], and can activate neighboring resting neutrophils in a LTB 4 receptor-dependent manner [138]. Thus, the exosomal pool of LTB 4 acts in an autocrine fashion to sensitize neutrophils towards a primary chemoattractant, and then in a paracrine fashion to mediate recruitment of neighboring neutrophils to augment inflammation.…”
Section: Potential Role Of Exosomes In Airway Remodeling During Latementioning
confidence: 99%
“…Neutrophil migration responds to gradients of exogenous and autocrine/paracrine chemokines (e.g., IL-8), cytokines (e.g., tumor necrosis factor α), as well as bioactive lipids (e.g., leukotriene B 4 (LTB 4 )) [45, 46]. Dynamic expression of specific receptors to these chemokines, cytokines, and bioactive lipids is critical to neutrophil migration.…”
Section: Reviewmentioning
confidence: 99%